How finance works : the HBR guide to thinking smart about the numbers - Desai, Mihir A. (Mihir Arvind), 1968- (Boston, Massachusetts : Harvard Business Review Press, 2019)
If you're not a numbers person, then balance sheets and financial jargon can be intimidating and easy to ignore. But if you want to advance in your career, it's crucial that you are able to make smart financial decisions and develop the confidence to clearly communicate those decisions to others. In How Finance Works, Mihir Desai--a professor at Harvard Business School and author of the widely praised book The Wisdom of Finance--guides you into the complex but endlessly fascinating world of finance and demystifies it in the process. Through entertaining stories, interactive exercises, full-color visuals, and a conversational style that belies the topic, Desai tackles a broad range of subjects that will give you the skills and knowledge you need to finally understand how finance works. These include: The ins and outs of balance sheets, and how different financial levers can affect a company's performance How companies fund their operations and investments in different ways Why finance is concerned with cash flow versus profits How value is created, measured, and maximized The importance of capital markets in helping companies grow Whether you're a student or manager, an aspiring CFO or entrepreneur, How Finance Works is the colorful and interactive guide you need to help you start thinking more deeply about the numbers.
Introduction -- Financial analysis: using ratios to analyze performance- all while playing a game -- The finance perspective: why finance is obsessed with cash and the future -- The financial ecosystem: understanding the who, why, and how of capital markets -- Sources of value creation: risk, costly capital, and the origins of value -- The art and science of valuation: how to value a home, an education, a project, or a company -- Capital allocation: how to make the most important decisions facing CEOs and CFOs -- Conclusion.
Includes bibliographical references and index.
Keywords: Finance; Business enterprises -- Finance